PROCENTAGE OF E-COMMERCE UTILIZATION AMONG UIN MAULANA MALIK IBRAHIM MALANG STUDENTS - Hidhayat, Ahmad Rizkyka Agung; Yudistira, Setya; Dwiyanto, Felix Andika (Letters in Information Technology Education (LITE), 2019)
This study aims to discover the influence of e-commerce on student life, both in terms of understanding and its use. The variables analyzed include the level of understanding, the experience of a transaction through e-commerce, reasons for choosing e-commerce, e-commerce knowledge sources, and a list of e-commerce sites they have used. Respondents were students of the State Islamic University of Maulana Malik Ibrahim Malang. A simple random sampling technique used in this study. As for the data collection, using a questionnaire technique. The obtained data will be processed and analyzed. Generally, the results of the study explain that most students know ecommerce, but the use is still not optimal, even very less.